Design and Development of Carborne Survey Equipment - S Syarbaini; B Bunawas; I.P. Susila (Atom Indonesia, 2015)
In most nuclear and radiological emergencies involving the release of radioactive materials to environment, it is important that data on the geographic distribution of potentially hazardous radioactive materials be quickly presented to the authorities. The mobile radiation detection system makes it possible to measure radioactive materials in the environment at random places because of its easy mobility from place to place. The purpose of the work is to develop a mobile radiation detection system to measure gamma exposure rate, radioactive material on the ground and airborne radioactive particulate in the environment quickly. In this work, we have developed a carborne survey equipment system consisting of three gamma ray detectors, one airbome radioactive particulate sampler, a GPS (Global Positioning System), meteorological sensors, a data acquisition system and an operation software. Performance of the carborne survey equipment has been successfully demonstrated to measure iodine and argon release from medical isotope production facility on Serpong in western Java, Indonesia.Received: 04 October 2014; Revised:16 March 2015; Accepted: 23 March 2015